Russia-Ukraine war: Short-run production and labour market effects of the energy crisis - Christian Hutter; Enzo Weber (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2022)
With the Russian war against Ukraine, global economic conditions changed abruptly. We provide first causal evidence of effects of the energy crisis on Germany as Europe's most important economy. Combining cost structure data, national accounts and administrative labour market data, we identify effects in a sectoral panel setting. The results show that via the channel of energy intensity, production decreased by about 1 percent with the onset of the war, but turnover increased, mirroring sales from stock. Firms safeguard employment via short-time work with 10 percent additional applications. Vacancy posting was reduced already in anticipation by 8 percent. – – Mit dem russischen Krieg gegen die Ukraine änderten sich schlagartig die weltwirtschaftlichen Rahmenbedingungen. Wir liefern erste kausale Evidenz für Effekte der Energiekrise in Deutschland als wichtigster Volkswirtschaft Europas. Durch die Kombination von Kostenstrukturdaten, Daten der Volkswirtschaftlichen Gesamtrechnungen und administrativen Arbeitsmarktdaten identifizieren wir Effekte in einem Branchen-Panel. Die Ergebnisse zeigen, dass über den Kanal der Energieintensität die Produktion mit Kriegsbeginn um rund 1 Prozent zurückging, der Umsatz jedoch stieg, was Lagerabbau widerspiegelt. Unternehmen sichern Beschäftigung durch Kurzarbeit mit 10 Prozent zusätzlichen Anzeigen. Die Schaffung neuer Stellen wurde bereits im Vorfeld des Krieges um 8 Prozent reduziert .
Keywords: E23; H56; J63; Q43; 330; Russia-Ukraine war; energy; production; labour market; Germany